Effects of Pre-Diapause Temperature and Body Weight on the Diapause Intensity of the Overwintering Generation of Bactrocera minax (Diptera: Tephritidae). Issue 1 (27th February 2020) - Zhou, Zhixiong; Dong, Xiaolin; Su, Qi; Xia, Zhenzhou; Wang, Zailing; Yuan, Jiangjiang; Li, Chuanren
Abstract: The Chinese citrus fruit fly, Bactrocera minax (Enderlein), is an economically important pest of citrus. The fly has an obligatory pupal diapause in soil from November to March. However, techniques for predicting or determining the emergence of the adult have, thus far, not been well documented. In this study, we investigated the effects of different pre-diapause temperatures (8, 12, 16, and 20°C) and pupal body weight (five groups according to pupal weight: G-58, 55.0–61.0 mg; G-68, 65–71 mg; G-78, 75–81 mg; G-88, 85–91 mg; G-95, 92–98 mg) on pupal period (the indicator of diapause intensity). The pupal period of B. minax larvae pupated at 8°C was 193.41 d, which was significantly shorter than that of larvae incubated at higher temperatures, suggesting that there was a lower diapause intensity for larvae pupated at lower pre-diapause temperatures. There were also significant differences in the pupal periods at different pupal body weights. The pupal period of G-58 was significantly shorter than that of the heavier groups (G-88 and G-95), and the pupal period increased with increasing pupal body weight in the five groups. Moreover, the pupal period of B. minax significantly and positively correlated to pupal body weight. These findings demonstrate that the pre-diapause temperature and pupal body weight are suitable indicators for predicting the pupal period of overwintering individuals, and the results of this study will contribute to the development of new and effective strategies for predicting the occurrence and population dynamics of B. minax adult.